How Does Job‐Protected Maternity Leave Affect Mothers’ Employment? - Baker, Michael; Milligan, Kevin (Journal of Labor Economics, 2008)
We examine the impact of maternity leaves on the period mothers are away from work postbirth and the likelihood they return to their prebirth employer. We use the introduction and expansion of statutory job-protected maternity leave entitlements in Canada to identify these effects. We find that modest leave entitlements of 17-18 weeks do not change the amount of time mothers spend away from work. In contrast, longer leaves do have a substantive impact on behavior, leading to more time spent at home. We also find that all entitlements we examined increase job continuity with the prebirth employer. (c) 2008 by The University of Chicago.